Ketahanan Varietas Padi terhadap Nematoda Pucuk Putih Aphelenchoides besseyi: The Resistance of Rice Varieties Against White Tip Nematode Aphelenchoides besseyi - Imamah, Annisa Nur; Supramana, Supramana; Damayanti, Tri Asmira (Jurnal Fitopatologi Indonesia, 2025)
The Resistance of Rice Varieties Against White Tip Nematode Aphelenchoides besseyiWhite tip disease on rice caused by Aphelenchoides besseyi is considered as a new important disease and it had widely distributed in Indonesia. The utilizing of resistant varieties is one of the best methods to control A. besseyi. However, there is no information regarding the resistance of rice varieties to A. besseyi in Indonesia. Nine rice varieties were evaluated for their resistance response to A. besseyi by inoculating 500 nematode per plant. Nematode A. besseyi was infested at the anthesis phase by spraying the nematode suspension onto the panicles followed by observation on panicle length, number of grains, number of full and empty grains, weight of 100 full grains, number of nematodes and expression of the PBZ1 gene of rice. Expression of PBZ1 gene was conducted by one-step reverse transcription-polymerase chain reaction (RT-PCR) using a specific primer PBZ1F and PBZ1R. Based on yield parameters, A. besseyi population, and PBZ1 gene expression, the resistance response of rice varieties to A. besseyi infestation was differentiated into three categories, namely resistant (‘Ciherang’, ‘Utri Merah’, and ‘Utri Rajapan’), tolerant (‘Inpago 7’, ‘IPB 3S’, ‘Prima’, and ‘Situ Bagendit’) and susceptible (‘Inpara 3’ and ‘Inpara 4’). Aphelenchoides besseyi’s infestation induces PBZ1 gene expression in the tested varieties at different intensities depending on their level of resistance. ‘Ciherang’, ‘Inpago 7’, ‘Situ Bagendit’, ‘Utri Merah’, and’ ‘Utri Rajapan’ showed high PBZ1 gene intensity both before and after A. besseyi infestation. The high intensity PBZ1 gene expression before A. besseyi infestation showed that this varieties have a potential source of resistant to A. besseyi. Based on the results there is a correlation between the high expression of PBZ1 gene with the resistance of rice varieties to A. besseyi.